Characterization of poly-β-hydroxybutyrate producing halophilic bacteria and nutrient optimization for its maximum production - PATIENCE, MAALDU; SINGH, SURENDER; KAUSHIK, RAJEEV (The Indian Journal of Agricultural Sciences, 2021)
An experiment was conducted at the Indian Agricultural Research Institute, New Delhi (2017-18) to report the identification of halophilic poly-ß-hydroxybutyrate (PHB) producing bacteria and optimization of process parameters for maximum PHB recovery. The phylogenetic analysis classified the isolates into bacterial phylum α, γ-Proteobacteria, and Firmicutes. Halomonas sp. KB7 and Stenotrophomonas maltophila B11 produced maximum PHB in mineral salt media having optimized C and N concentration with 10% NaCl. Optimizing media increased PHB production from 23.80–73.7% w/w for Halomonas sp and 29.5–78.3 % w/w for S. maltophila.